The double anaerobic threshold in heart failure: MECKI score database overview - Sara Rovai; Denise Zaffalon; Marco Cittar; Luca Francesco Felli; Elisabetta Salvioni; Arianna Galotta; Irene Mattavelli; Cosimo Carriere; Massimo Mapelli; Marco Merlo; Carlo Vignati; Gianfranco Sinagra; et al. (ESC Heart Failure, 2022)
Abstract Aims In heart failure (HF), anaerobic threshold (AT) may be indeterminable but its value held a relevant prognostic role. AT is evaluated joining three methods: V‐slope, ventilatory equivalent, and end‐tidal methods. The possible non‐concordance between the V‐slope (met AT) and the other two methods (vent AT) has been highlighted in healthy individuals and named double threshold (DT). Methods and results We reanalysed 1075 cardiopulmonary exercise tests of HF patients recruited in the Metabolic Exercise test data combined with Cardiac and Kidney Indexes (MECKI) score database. We identified DT in 43% of cases. Met AT precedes vent AT being met–ventΔVO2 221 (interquartile range: 129–319) mL/min. Peak VO2, 1307 ± 485 vs. 1343 ± 446 mL/min (63 ± 17 vs. 63 ± 17 percentage of predicted), was similar between DT+ and DT− patients. Differently, DT+ showed a lower ventilatory vs. carbon dioxide production (VE/VCO2) slope (29.6 ± 6.1 vs. 31.0 ± 6.3), a lower peak exercise end‐tidal oxygen tension (PetO2) 115.3 (111.5–118.9) vs. 116.4 (112.4–120.2) mmHg, and a higher carbon dioxide tension (PetCO2) 34.2 (30.9–37.1) vs. 32.4 (28.7–35.5) mmHg. Vent AT showed a significant higher VO2, 957 ± 318 vs. 719 ± 252 mL/min, VCO2, 939 ± 319 vs. 627 ± 226 mL/min, ventilation, 31.0 ± 8.3 vs. 22.5 ± 6.3 L/min, respiratory exchange ratio, 0.98 ± 0.08 vs. 0.87 ± 0.07, PetO2, 108 (104–112) vs. 105 (101–109) mmHg, PetCO2, 37 (34–40) vs. 36 (33–39) mmHg, and VE/VO2 ratio, 33.5 ± 6.7 vs. 32.6 ± 6.9, but lower VE/VCO2 ratio, 33 (30–37) vs. 36 (32–41), compared with met AT. At 2 year survival by Kaplan–Meier analysis, even adjusted for confounders, DT resulted not associated with survival. Conclusions Double threshold is frequently observed in HF patients. DT+ is associated to a decreased ventilatory response during exercise.